L‐Citrulline supplementation improves glucose and exercise tolerance in obese male mice. Issue 2 (15th January 2020) - Eshreif, Amina; Al Batran, Rami; Jamieson, K. Lockhart; Darwesh, Ahmed M.; Gopal, Keshav; Greenwell, Amanda A.; Zlobine, Igor; Aburasayn, Hanin; Eaton, Farah; Mulvihill, Erin E.; Campbell, Jonathan E.; Seubert, John M.; et al.
Abstract : New Findings: What is the central question of the study? Does the action of l ‐citrulline, which has been shown to augment performance in animals and athletes, possibly via increasing mitochondrial function, translate to obese animals, and does this improve glycaemia? What is the main finding and its importance? Chronic supplementation with l ‐citrulline improves not only exercise capacity, but also glycaemia in obese mice, which would be beneficial as obese individuals are at increased risk for type 2 diabetes. However, l ‐citrulline supplementation also caused a mild impairment in insulin signalling and insulin tolerance in obese mice. Abstract: l ‐Citrulline is an organic α‐amino acid that has been shown to have a number of salutary actions on whole‐body physiology, including reducing muscle wasting and augmenting exercise and muscle performance. The latter has been suggested to arise from elevations in mitochondrial function. Because enhancing mitochondrial function has been proposed as a novel strategy to mitigate insulin resistance, our goal was to determine whether supplementation with l ‐citrulline could also improve glycaemia in an experimental mouse model of obesity. We hypothesized that l ‐citrulline treatment would improve glycaemia in obese mice, and this would be associated with elevations in skeletal muscle mitochondrial function. Ten‐week‐old C57BL/6J mice were fed either a low‐fat (10% kcal from lard) or a high‐fat (60% kcal from lard) diet, while receiving drinking water supplemented with either vehicle or l ‐citrulline (0.6 g l −1 ) for 15 weeks. Glucose homeostasis was assessed via glucose/insulin tolerance testing, while in vivo metabolism was assessed via indirect calorimetry, and forced exercise treadmill testing was utilized to assess endurance. As expected, obese mice supplemented with l ‐citrulline exhibited an increase in exercise capacity, which was associated with an improvement in glucose tolerance. Consistent with augmented mitochondrial function, we observed an increase in whole body oxygen consumption rates in obese mice supplemented with l ‐citrulline. Surprisingly, l ‐citrulline supplementation worsened insulin tolerance and reduced insulin signalling in obese mice. Taken together, although l ‐citrulline supplementation improves both glucose tolerance and exercise capacity in obese mice, caution must be applied with its broad use as a nutraceutical due to a potential deterioration of insulin sensitivity. Abstract :